The value of diversity: can a company’s gender diversity levels have a positive influence on its financial performance? - Mazon, Bruna (2019)
This study aims to understand whether higher levels of gender diversity in top 150 global fortune 500 corporations’ board of directors has a positive impact on their financial performance. Also, it seeks to understand what are the drives that lead to this impact, if proven, and how companies can act to reach those levels of gender diversity via case studies. The exploration of the way diversity impacts the private industry, not only in brazil, but all over the globe, is important to increase discussions regarding discrimination and harassment towards sex differences. Moreover, it intends to address a potential economic value increase to society as a whole.